2022
DOI: 10.3390/d14070535
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Flora in Adult Females of the Rearing Population of Ambrosia Beetle Euwallacea interjectus (Blandford) (Coleoptera: Curculionidae: Scolytinae): Does It Differ from the Wild Population?

Abstract: Ambrosia beetles bore into host trees, and live with fungi symbiotically that serve as a food source. However, it is challenging to directly observe these beetles in the wild. In this study, Euwallacea interjectus Blandford (Coleoptera: Curculionidae: Scolytinae), a pest of fig trees in Japan, were reared under artificial conditions to emulate the behavior of Ambrosia beetle. Fungi were isolated from the adult females of E. interjectus to identify the species associated with secondary symbiosis. In total, nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Nonetheless, of the 22 species of ophiostomatoid fungi isolated from adult females of wild and reared E. interjectus , at least two dominant fungi, Fusarium kuroshium (Na, Carrillo et Eskalen ex Sand.-Den. et Crous) [ 18 ] and Neocosmospora metavorans (Al-Hatmi et al) [ 19 ], respectively, may affect the progression of FWD. Morita et al [ 7 ] reported that inoculation with C. ficicola killed the ‘Horaishi’ fig saplings.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, of the 22 species of ophiostomatoid fungi isolated from adult females of wild and reared E. interjectus , at least two dominant fungi, Fusarium kuroshium (Na, Carrillo et Eskalen ex Sand.-Den. et Crous) [ 18 ] and Neocosmospora metavorans (Al-Hatmi et al) [ 19 ], respectively, may affect the progression of FWD. Morita et al [ 7 ] reported that inoculation with C. ficicola killed the ‘Horaishi’ fig saplings.…”
Section: Introductionmentioning
confidence: 99%